2009
DOI: 10.1007/s12098-009-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia and metastatic calcification in a neonate with subcutaneous fat necrosis

Abstract: We report a 30-day-old baby with subcutaneous fat necrosis and symptomatic hypercalcemia, who developed metastatic calcification in the subcutaneous tissue, kidneys, pericardium and brain. The baby also had anemia, hypertriglyceridemia and hypercholesterolemia. He was managed with intravenous saline, furosemide, oral steroids and bisphosphonates and improved with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
5
0
3
Order By: Relevance
“…Some authors reported an association with elevated prostaglandin levels that can lead to osteoclast activation and calcium release from granulomas or necrotic fat [37]. For others, hypercalcemia is believed to be caused by an excessive extra renal production of 1,25-dihydroxyvitamin D [17,33,34,36,38] by the granulomatous macrophages, as observed in other granulomatous inflammations, such as sarcoidosis [39] which increases the intestinal calcium uptake [20]. These complications were not detected in our patients.…”
Section: Filippi Et Al the Journal Of Maternal-fetal And Neonatalmentioning
confidence: 48%
See 1 more Smart Citation
“…Some authors reported an association with elevated prostaglandin levels that can lead to osteoclast activation and calcium release from granulomas or necrotic fat [37]. For others, hypercalcemia is believed to be caused by an excessive extra renal production of 1,25-dihydroxyvitamin D [17,33,34,36,38] by the granulomatous macrophages, as observed in other granulomatous inflammations, such as sarcoidosis [39] which increases the intestinal calcium uptake [20]. These complications were not detected in our patients.…”
Section: Filippi Et Al the Journal Of Maternal-fetal And Neonatalmentioning
confidence: 48%
“…It usually occurs between 2 and 16 weeks, when SFN begins to resolve and may either be asymptomatic or manifest with failure to thrive, lethargy, irritability, hypotonia, vomiting and, in severe cases, calcification of the soft tissues. Nephrolithiasis, nephrocalcinosis, renal failure, metastatic calcification in the pericardium and brain, and also cardiac arrest have been described [34][35][36]. Some authors reported an association with elevated prostaglandin levels that can lead to osteoclast activation and calcium release from granulomas or necrotic fat [37].…”
Section: Filippi Et Al the Journal Of Maternal-fetal And Neonatalmentioning
confidence: 99%
“…Nair et al [140] reported a 30-day-old infant with subcutaneous fat necrosis and symptomatic hypercalcemia, who developed metastatic calcification in the subcutaneous tissue, kidneys, pericardium and brain. The infant had anemia, hypertriglyceridemia and hypercholesterolemia.…”
Section: Resultsmentioning
confidence: 99%
“…Con respecto al EN entre los factores de riesgo descritos están: RN muy graves, prematuros con bajo peso al nacer, sepsis, cardiopatías congénitas, entre otras 18 . Se asocia con una alta tasa de mortalidad, alrededor del 75% 19 .…”
Section: Discussionunclassified